Hands-On Azure Digital Twins : a Practical Guide to Building Distributed IoT Solutions - Meijers, Alexander (Packt Publishing, Limited, 2022)
Build your own digital twin in no time! Key Features Build and design simple to complex digital twins solutions Create end-to-end solutions with Azure Digital Twins Integrate the Azure Digital Twins service with other Azure services to provide even richer solutions Book Description In today's world, clients are using more and more IoT sensors to monitor their business processes and assets. Think about collecting information such as pressure in an engine, the temperature, or a light switch being turned on or off in a room. The data collected can be used to create smart solutions for predicting future trends, creating simulations, and drawing insights using visualizations. This makes it beneficial for organizations to make digital twins, which are digital replicas of the real environment, to support these smart solutions. This book will help you understand the concept of digital twins and how it can be implemented using an Azure service called Azure Digital Twins. Starting with the requirements and installation of the Azure Digital Twins service, the book will explain the definition language used for modeling digital twins. From there, you'll go through each step of building digital twins using Azure Digital Twins and learn about the different SDKs and APIs and how to use them with several Azure services. Finally, you'll learn how digital twins can be used in practice with the help of several real-world scenarios. By the end of this book, you'll be confident in building and designing digital twins and integrating them with various Azure services. What you will learn Understand the concept and architecture of Azure Digital Twins Get to grips with installing and configuring the service and required tools Understand the Digital Twin Definition Language (DTDL) and digital twin models Explore the APIs and SDKs available to access the Azure Digital Twins services Monitor, troubleshoot, and secure digital twins Discover how to build, design, and integrate applications with various Azure services Explore real-life scenarios with Azure Digital Twins Who this book is for This book is for Azure developers, Azure architects, and anyone who wants to learn more about how to implement IoT solutions using Azure Digital Twins and additional Azure services. Prior experience using the Azure Portal and a clear understanding of building applications using .NET will be helpful.